Poly(lactide-co-glycolide) nanoparticles embedded in a micropatterned collagen scaffold for neuronal tissue regeneration. Issue 7 (3rd May 2017) - Giampetruzzi, Lucia; Blasi, Laura; Quarta, Alessandra; Argentiere, Simona; Cella, Claudia; Salvatore, Luca; Madaghiele, Marta; Gigli, Giuseppe; Sannino, Alessandro
ABSTRACT: Micropatterned collagen scaffold with axially oriented pores embedded with poly(lactide-co-glycolide) nanoparticles (PLGA NPs) was synthesized and characterized. Two different concentrations of PLGA nanoparticles have been tested and the experimental results indicate that the concentration affects the release kinetic, whereas the stiffness, the crosslink density, and the degradation rate of the collagen matrix are comparable to bare scaffold. Further, the proposed crosslinking procedure provides a resistance to thermal and enzymatic degradation, thereby promoting the persistence of scaffold for a period of time compatible with nerve regeneration. GRAPHICAL ABSTRACT: